Tondo Community School educational as a catalyst for community development - Au, Kate Chrisgracen Y. (College of Architecture, University of the Philippines Diliman, 2020)
Within the affluent and concentrated urbanized cores of the cities lie the many voids of excluded communities, constantly trapped in the hands of poverty without any means of escape. Included in the impoverished voids of Manila is the Vitas Community of Barangay 105, Tondo, comprised of the Happy Land and the Aroma Compound. This informal settlement community is mostly known as the scavenging community of Manila, who used to be the residents of the nearby Smokey Mountain dumpsite area. In the pursuit of aiding these communities towards development, the role of education, amongst all approaches, proved to be most effective catalyst for community development. However, a thorough study of the educational situation in Tondo shows that, contrary the common notion, the presence of a large number of traditional educational institutions alone, cannot stop the proliferation of the high index of out-of-school youth (OSY) and low literacy rate in Tondo. Therefore, a shift to a more appropriate educational model is needed to cater to the unique needs of its impoverished constituents. With this, the idea of the "Redefined Community School" was conceived. The "Redefined Community School" is an alternative community-based educational impoverished communities, as the critical foundation towards their community's development, it differs with the existing public schools and international community schools, in a way that it is: all-inclusive (caters for every member of the community of all ages, from daycare to livelihood programs), accessible (open and not isolated from the community) and adaptable (conforms to the local community's unique needs & resources). In the crucial process of reaching out and learning about the community members of Tondo and how they want their community school to adapt to their needs, project-based learning, or learning through real-world problems instead of traditional teacher-based instruction, proved to be most appropriate approach for their school. As a result, the school was designed with the main concept of "Bottom-Up Educational Influence". where educational influence roots from the bottom community level towards the upper formal schools levels, through (1) creating a learning network with different community partners on the ground level, (2) blurring its borders to let the outside community into its upper levels and (3) inserting various shared learning areas all over the school to create a dynamic and continuous learning corridor. The design output of a community school model in Tondo is a cluster of buildings with flexible modular units, resembling a micro city with the spatial compositions of the urban landscape. The network of buildings is open and diversified with typological places, such as plazas and courtyards, to encourage the community into the site and to nurture a familiar feeling from everyday life. These buildings are connected with a labyrinth of ramps, that are displaced into different learning areas, increasing opportunity for both students and the community to learn together in a real world setting ; hence, propounding a school-to-city or city-to-school communication.